To find an equation that has the same solution for \( x \) as the equation \( x - 12 = 40 \), we first solve the original equation:
\[ x - 12 = 40 \]
Adding 12 to both sides, we get:
\[ x = 40 + 12 \] \[ x = 52 \]
Now, we need to check which of the given options also leads to \( x = 52 \).
-
\( 12 - x = 40 \)
Solving this: \[ -x = 40 - 12 \] \[ -x = 28 \quad \Rightarrow \quad x = -28 \quad (\text{not equal to 52}) \]
-
\( x/4 = 13 \)
Solving this: \[ x = 4 \times 13 \] \[ x = 52 \quad (\text{this one works}) \]
-
\( x + 12 = -40 \)
Solving this: \[ x = -40 - 12 \] \[ x = -52 \quad (\text{not equal to 52}) \]
-
\( x^2 = 14 \)
Solving this: \[ x = \sqrt{14} \quad \text{or} \quad x = -\sqrt{14} \quad (\text{not equal to 52}) \]
Therefore, the equation that has the same solution for \( x \) as \( x - 12 = 40 \) is:
\( x/4 = 13 \).